Efeitos da dessincronização circadiana nos estágios iniciais da ontogênese em parâmetros comportamentais relacionados à ritmicidade, metabolismo, memória, ansiedade e depressão em ratos wistar adultos - Pugliane, Karen Cristina (2021)
The synchrony of organisms to their environment has a clear adaptive value, and changes in their temporal organization may impair physiological functions and behavior. Circadian desynchronization is associated with metabolic and cognitive impairment in human and nonhuman animals. In mammals, the circadian system continues to develop during the postnatal period, and the consequences of early rhythmicity disorders in latter ontogenetic phases are still not well understood. The aim of the present study was to evaluate the circadian rhythmicity of locomotor activity, weight, food and water consumption, anxiety-like and depressive likebehavior, as well as memory abilities in adult male Wistar rats submitted to a forced internal circadian desynchronization protocol in early ontogenetic phases. Animals were exposed to a symmetrical light-dark cycle 11:11 (T22 protocol) in infancy and adolescence. In the Infancy D group, rats were exposed to the T22 protocol in the uterine and lactation phases; in the Adolescence D group, rats were exposed to the T22 protocol from weaning (P22) to P63, and the Control group was kept in a 12:12 light-dark cycle. All animals were resynchronized to LD 12:12 (T24) afterwards and were tested in adulthood. We used the open field test (OF), novel object recognition test (NOR), object-in-place recognition task (OiP), sucrose preference test (SP), and passive avoidance test (PA), which evaluate, respectively: anxiety-like behavior, recognition memory, associative spatial memory, depressive-like behavior and aversive memory. We found that the Infancy D group presented lower robustnessof the rhythm after resynchronized to T24 in adulthood, relatively higher body mass and were impaired in NOR and OiP tasks, which support the notion that the impairment was higher in this ontogenetic phase. On the other hand, the Adolescence D group had relatively lower body mass in adulthood, anhedonia and higher bouts of incomplete self-grooming, as well as impairment in the OiP task, which suggests an increased susceptibility to mood disorders, spatial memory impairment and weight loss. Overall, these findings showed that the exposure to the T22 forced desynchronization protocol in early ontogenetic phases can lead to differential and long-lasting effects in behavioral parameters related to rhythmicity, metabolism, memory, and affective disorders.